2001
DOI: 10.1080/mmy.39.1.123.127
|View full text |Cite
|
Sign up to set email alerts
|

Adherence of clinical isolates of Saccharomyces cerevisiae to buccal epithelial cells

Abstract: A number of isolates of Saccharomyces cerevisiae have been associated with disease in immunocompromised individuals. Such isolates display a variety of characteristics that enable colonization and persistence in the host. The aim of the work presented here was to establish whether clinical isolates of S. cerevisiae were capable of adhering to epithelial tissue. Adherence to host tissue has been shown to be crucial to the virulence of the pathogenic yeast Candida albicans, and identi cation of this ability in S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 29 publications
(31 reference statements)
1
4
0
Order By: Relevance
“…Results showed that both clinical (vaginal) and nonclinical (dietetic and biotherapeutic) isolates possess a limited, but detectable ability to adhere to endothelial, and particularly to epithelial cell lines, as compared to the faecal ** */** isolate and the reference wine strain, which were much less adherent, and to C. albicans, which possess a higher adherence potential. A similar result was reported for the adhesion of S. cerevisiae clinical and non-clinical isolates to Caco-2 and buccal epithelial cells [30,46]. This ability to adhere to host cells can be considered as a virulence factor contributing to the pathogenicity of S. cerevisiae isolates.…”
Section: Discussionsupporting
confidence: 81%
“…Results showed that both clinical (vaginal) and nonclinical (dietetic and biotherapeutic) isolates possess a limited, but detectable ability to adhere to endothelial, and particularly to epithelial cell lines, as compared to the faecal ** */** isolate and the reference wine strain, which were much less adherent, and to C. albicans, which possess a higher adherence potential. A similar result was reported for the adhesion of S. cerevisiae clinical and non-clinical isolates to Caco-2 and buccal epithelial cells [30,46]. This ability to adhere to host cells can be considered as a virulence factor contributing to the pathogenicity of S. cerevisiae isolates.…”
Section: Discussionsupporting
confidence: 81%
“…The number of IPEC-J2 cells that grew to 70% confluence was estimated based on the counting results of IPEC-J2 cells that were sub-cultured in parallel. The proportion of K. slooffiae numbers to IPEC-J2 cell numbers was chosen according to previously described co-culture procedures [ 50 54 ]. The representative pictures for the co-culture of K. slooffiae and IPEC-J2 cells were shown in Additional file 4 : Fig.…”
Section: Methodsmentioning
confidence: 99%
“…A growing number of S. cerevisiae infections in humans have recently been reported (14). As a result, S. cerevisiae is also regarded as an emerging opportunistic pathogen that can cause clinically relevant infections in different patient types and body sites (15)(16)(17). One clinical strain (YJM145), derived from a yeast isolated from an AIDS patient with S. cerevisiae pneumonia (18), has been studied extensively as a model for fungal infections (19)(20)(21)(22)(23)(24).…”
mentioning
confidence: 99%